Communal Culture Value on Housing Transformation: Empirical Exploration from Indonesia - Ernawati, Rita; Setijanti, Purwanita; Santosa, Happy Ratna (EMARA: Indonesian Journal of Architecture, 2025)
Culture became important consideration in housesing design. House form is the consequence of a whole range of socio-cultural factor, not simply physical factor. Housing is more than a place to live, however also preserving certain values. The aim of this research is to reveal the significant relation of housing transformation and communal culture value. This study applies the case study approach through a qualitative analysis of the housing transformation phenomenon. Housing transformation is a process of adjusting space to fulfill certain functions based on the needs of the users, that fit with the culture value expression of the inhabitants. This resarch formulated four significant factor determine housing transformation factor in kampung, that are economic condition, housing condition, occupant condition and kampung improvement. House transformation was related to the communal cultural values ​​since the construction process to utilization. The mutual understanding on make the process of housing transformation can be carried out without causing conflicts over the use of space in kampung. House construction is also carried out with the support of neighbors since the exsistance of togetherness and gotong royong. In terms of creating better image of the kampung, solidarity velue was important to encorage the community working together improving kampung and their house. The mutual cooperation, community understanding, togetherness and solidarity were important in maintaining the commitment and social value among the inhabitants to live and grow together. Kampung is a model of settlement where the communal values are important in sustaining the harmony of urban living.